Highly enantioselective Pd-catalyzed synthesis of P-stereogenic supramolecular phosphines, self-assembly, and implication - Koshti, Vijay S.; Mote, Nilesh R.; Gonnade, Rajesh G.; Chikkali, Samir H. (Organometallics, 2015)
Metal-catalyzed asymmetric addition of a secondary phosphine to an aryl halide is one of the most efficient and reliable approaches for the construction of enantiopure carbon phosphorus bonds. An isolated Pd(II) complex (5) catalyzes the carbon phosphorus coupling reaction between tolylphenylphosphine (la) and 3-iodophenylurea (2b), which proceeds with an unprecedented enantiomeric excess (ee) of 97%. The generality of the strategy has been demonstrated by preparing a small library of a new class of P-stereogenic phosphines with an in-built hydrogen bonding motif for the first time. The P-stereogenic phosphines self-assemble on a metal template via deliberately installed hydrogen-bonding motifs and mimic the bidentate ligand coordination. Interestingly, when it was employed in asymmetric hydrogenation, the supramolecular phosphine {1-(3-(phenyl(o-toly)phosphanyl)pheny)ureal} (6b) produced the corresponding hydrogenated product with the highest enantiomeric excess of 99% along with excellent conversion, demonstrating the potential of these enantioenriched P-chirogenic supramolecular phosphines in asymmetric catalysis.